P/E effect and managerial ownership: How managerial ownership affects stock returns with different price-to-earnings ratios - Riikonen, Noora (My University, 2016)
Investors are constantly seeking different strategies to get their portfolios to earn superior returns. One of the widely studied investment strategies suggests that companies with high managerial ownership perform on average better than companies with low managerial ownership. A prior empirical research is shown that investing in companies with high CEO ownership lead to large abnormal returns (Ruenzi & Von Lilienfeld-Toal 2014). The main explanations for better performance of companies with high managerial ownership seem to be the alignment of manager and shareholder’s interest. Houmes and Chira (2015) find that managerial ownership diminishes the tendency of low price-to-earnings companies to earn higher returns. This thesis aims to extend the Houmes & Chira’s (2015) research by studying whether companies with high managerial ownership still earn positive abnormal returns when company’s P/E ratio is considered. The empirical part of this study uses a panel dataset of listed companies in the Untied States over the years 2009–1014. The existing studies of managerial ownership rely more on firm’s performance with accounting profit and Tobin’s Q. Carhart’s (1997) four-factor model and multivariate regression are used to evaluate portfolio returns. The findings of the empirical part show that portfolio with high managerial ownership and low P/E does not generate positive abnormal returns. The results from the multivariate regression are in line with results of Houmes & Chira’s (2015). The P/E effect seems to be reverse among companies with high managerial ownership.
Keywords: Managerial ownership; Price-to-earnings ratio; Stock returns; fi=Laskentatoimi ja rahoitus|en=Accounting and Finance|; fi=Master's Degree Programme in Finance|